Green beauty care choices: Mediating effects of self-generated word of mouth on Gen Z buying behavior - Athia, Ita; Amin, Muh. Sirojuddin; Mohd Salleh, Muhammad Zulfaris (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2024)
With growing concern about environmental issues, purchasing behavior has significantly changed, especially among women. They now seek extensive information about environmentally friendly beauty care brands, often relying on word of mouth to guide their decisions. Existing studies on word of mouth largely focus on the receiver perspective. However, there is a notable gap in studies examining the impact of word of mouth on the senders themselves. Motivated by addressing this significant gap in the literature, we dedicate this exploratory study to investigating sender outcomes, such as purchase decisions. To gather relevant data, we used purposive and snowball sampling methods, specifically targeting Indonesian Gen Z women who are aware of environmental issues and use beauty care products. Results from PROCESS Macro Model 4, based on responses from 253 respondents, show that the high perception of environmentally friendly beauty care product quality significantly affects both word of mouth and repurchase intention, both directly and indirectly. While an environmentally friendly brand image directly impacts repurchase intention, it does not influence WOM. This suggests that Gen Z is more likely to tell and share their experiences about the benefits and effectiveness of high-quality, natural ingredient beauty care products rather than the brand’s environmental commitments and activities.